2006
DOI: 10.1007/s10762-006-9123-6
|View full text |Cite
|
Sign up to set email alerts
|

SIMULATION OF CARBON NANOTUBE THz ANTENNA ARRAYS

Abstract: A novel THz antenna structure, made of carbon nanotube arrays is suggested.Using CST MICROWAVE STUDIO (CST MWS), the capabilit ies of carbon nanotube terahertz (THz) antenna arrays have been simulated. The dependence of gain, upon geometrical factors, e.g., nanotube diameter, nanotube length and the inter-tubes distance, is shown. The directivity patterns of antenna arrays and the surface current distribution of an antenna have been shown by simulation. These results could be used in the design ofcarbon nanotu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Ref. 29 shows that they can be used in THz frequency also. But the research is still in nascent stage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. 29 shows that they can be used in THz frequency also. But the research is still in nascent stage.…”
Section: Resultsmentioning
confidence: 99%
“…Reference [29] discusses about a novel THz antenna made of array of Carbon nanotubes. Finite length dipole antennas can be formed with CNT.…”
Section: Terahertz Antennasmentioning
confidence: 99%
“…CNT antennas have been examined for communication between electronic nanodevices and the outside macroscopic world [7][8][9][10][11][12][13][14]. The exploitation of CNTs has yielded the extreme miniaturization of antennas for microwave, terahertz, infrared, and optical applications, whereby radiating elements are presently a few nanometers in size.…”
Section: Introductionmentioning
confidence: 99%
“…In terahertz and infrared frequency range, the radiation characteristics of CNT dipole antenna arrays have been investigated by CST MICROWAVE STUDIO. It was shown that, N × N antenna arrays have a higher radiation efficiency than single CNT dipole antenna [10,11]. For the CNT antennas array without coupling, the array factor approach is used to investigate the antenna radiation pattern.…”
Section: Introductionmentioning
confidence: 99%